Governance and environmental management: an introduction - Tostes Vieira, Marta Lucía (2024)
In this 14th number, we organized the articles into three large blocks to address the main trends in research in our environment on governance and sustainable management,: the first, with six investigations linked to sustainable management tools for governance, such as risk management disasters, construction of scenarios, conservation of protected natural areas and contributions of economic sciences in cities such as Áncash, Piura, Ica and Chosica; the second, with three national investigations related to social management in environmental management, in Tacna, Lima (Ancón) and Loreto; and, finally, four very interesting international case studies in Mexico, Guatemala, Argentina and Ukraine. In this sense, the role of Revista Kawsaypacha: Sociedad y Medio Ambiente journal focuses on being a disseminator of validated scientific knowledge that sheds light on the main debates that the academy must contribute both to the training of committed professionals and directly to the design and implementation of solutions for environmental social problems, with the impetus of a heightened dialogue. That is why we hope that people who read these articles take away reflections on governance for sustainable management, with social management tools for environmental management, from a territorial perspective at a national and international level, which serve as a legacy, as well as for the promotion of sustainable development.